2010
DOI: 10.1007/s00404-010-1579-x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin 2,500 mg/day in the treatment of obese women with polycystic ovary syndrome and its effect on weight, hormones, and lipid profile

Abstract: The results of this study show that 2,500 mg daily dose of metformin in obese patients with PCOS is effective in the reduction of BMI, waist hip/ratio, LDL, serum insulin and increases SHBG. In general this dose was relatively safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Previous reports revealed that acarbose and metformin both had some beneficial effects on metabolic syndrome. Our finding was consistent with others [29][30][31][32] and revealed that acarbose and metformin could decrease plasma TC and non-HDL-C slightly in the three groups. The proportion of patients with optimal LDL-C levels with metformin treatment was higher than acarbose in better β-cell function group.…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports revealed that acarbose and metformin both had some beneficial effects on metabolic syndrome. Our finding was consistent with others [29][30][31][32] and revealed that acarbose and metformin could decrease plasma TC and non-HDL-C slightly in the three groups. The proportion of patients with optimal LDL-C levels with metformin treatment was higher than acarbose in better β-cell function group.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, obesity and insulin resistance are associated with pathogenesis of polycystic ovarian syndrome (PCOS), a condition characterized by a reduced frequency of ovulation, infertility, and hyperandrogenism in premenopausal women (67,68). Metformin's effect on weight in women with PCOS is not as well defined, depending on the population and study design (69)(70)(71)(72)(73)(74). However, a meta-analysis showed that metformin contributed to a decrease of body mass index (BMI) and waist to hip ratio (WHR) in 11 and 7 RCTs of PCOS women respectively, compared to placebo (75).…”
Section: Metformin Decreases Body Weight In Diabetic and Non-diabeticmentioning
confidence: 99%
“…Currently, metformin is one of the most produced oral antidiabetic drugs in the world and is considered the first-line treatment option managing type 2 diabetes mellitus . Recently, additional therapeutic actions have been described in other pathologies, such as polycystic ovary syndrome, obesity and hepatic steatosis, and potential uses in breast cancer [4, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%